The Corona Challenge to Higher Education - Peter Mayo (Culture e Studi del Sociale)
Covid-19 poses a number of challenges to Higher Education. It has turned the day to day world of academic life on its head.  University alternatives offer tenured academics a relatively safe adjustment to the changed scenario in stark contrast to other people for whom the current situation presents a choice: exposure or starvation. Precarious academics working part-time and according to definite contracts and students coming from humble backgrounds also face problems in this age of Corona. Furthermore, within the relatively safe ‘middle class’ context of secluded and virtually-mediated academic work and transaction, there are still issues to be considered bearing in mind to the future of Higher Education itself.